2019
DOI: 10.1016/j.diabet.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy, safety, and cardiovascular outcomes with once-weekly subcutaneous semaglutide in the treatment of type 2 diabetes: Insights from the SUSTAIN 1–7 trials

Abstract: In individuals with type 2 diabetes, glycaemic control and cardiovascular risk factor management reduces the likelihood of late-stage diabetic complications. Guidelines recommend treatment goals targeting HbA1c, body weight, blood pressure, and low-density lipoprotein cholesterol. Development of new treatments for type 2 diabetes requires an understanding of their mechanism and efficacy, as well as their relative effects compared to other treatment choices, plus demonstration of cardiovascular safety. Subcutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
96
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(151 citation statements)
references
References 43 publications
12
96
2
4
Order By: Relevance
“…1 Semaglutide is a GLP-1 analogue currently approved for once-weekly subcutaneous injection for treatment of type 2 diabetes, 2 and has been shown to decrease HbA1c and bodyweight effectively in patients who have uncontrolled hyperglycaemia on one or more oral glucose-lowering drugs. 3 Elimination of semaglutide occurs via multiple pathways involving both the liver and kidneys. 4 An oral semaglutide tablet has been developed, in which semaglutide is coformulated with the absorption enhancer, sodium N-(8-[2-hydroxybenzoyl]amino) caprylate, to facilitate semaglutide absorption across the gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…1 Semaglutide is a GLP-1 analogue currently approved for once-weekly subcutaneous injection for treatment of type 2 diabetes, 2 and has been shown to decrease HbA1c and bodyweight effectively in patients who have uncontrolled hyperglycaemia on one or more oral glucose-lowering drugs. 3 Elimination of semaglutide occurs via multiple pathways involving both the liver and kidneys. 4 An oral semaglutide tablet has been developed, in which semaglutide is coformulated with the absorption enhancer, sodium N-(8-[2-hydroxybenzoyl]amino) caprylate, to facilitate semaglutide absorption across the gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…The FIGHT trial, a multicentre, double-blind, placebo-controlled randomized clinical trial of HFrEF, revealed that the use of liraglutide did not lead to greater post-hospitalization clinical stability [143]. In SUSTAIN 6, involving 3297 patients with type 2 diabetes who were at high cardiovascular risk, the rate of cardiovascular death, nonfatal MI, or nonfatal stroke was significantly lower among patients receiving semaglutide than among those receiving placebo, an outcome that confirmed the noninferiority of semaglutide [144,145].…”
Section: Glucagon-like Peptide-1 (Glp-1)mentioning
confidence: 93%
“…A summary of selected efficacy outcomes from the SUSTAIN program is shown in Table 2. Subcutaneous semaglutide demonstrated superior and sustained reductions in HbA 1c versus all comparators, including other injectable therapies, and the 1 mg dose appears to have the greatest weight loss efficacy within the GLP-1RA class [22,25,26]. In addition, subcutaneous semaglutide was found to significantly reduce the risk of major adverse CV events in patients with T2D at high CV risk in the SUSTAIN 6 study [6], and is now approved by the FDA for reducing the risk of such events in patients with T2D and established CV disease [3].…”
Section: Subcutaneous Semaglutide: Efficacy Outcomes Of the Sustain Pmentioning
confidence: 94%
“…Semaglutide is a GLP-1RA that has high (94%) homology with human GLP-1 but has structural modifications to increase binding to serum albumin and delay degradation in the plasma, giving a long elimination half-life suitable for once-weekly administration by subcutaneous injection [3,18,19]. The clinical effects of subcutaneous semaglutide were investigated in the SUSTAIN program, which encompassed the full spectrum of diabetes care, including early therapy (SUSTAIN 1), and comparisons with other GLP-1RA therapies (exenatide ER [SUSTAIN 3], dulaglutide [SUSTAIN 7]), and with insulin therapy (SUSTAIN 4) [20][21][22][23][24]. A summary of selected efficacy outcomes from the SUSTAIN program is shown in Table 2.…”
Section: Subcutaneous Semaglutide: Efficacy Outcomes Of the Sustain Pmentioning
confidence: 99%